Perjanjian Nominee sebagai Sarana Penguasaan Hak Milik atas Tanah oleh Warga Negara Asing (WNA) Menurut Kitab Undang-Undang Hukum Perdata - Yosia Hetharie (Faculty of Law, Universitas Pattimura, 2019)
The main issues of concern in this study is still the practice of control of land ownership by foreigners through a nominee agreement by using the guise of citizen so as if it did not violate the Act. This action was legalized by a notary / PPAT that in fact understand clearly applicable law. Therefore, this study aims to analyze the validity, binding strength, and as a result of the implementation of treaty law nominee in the control rights to land by foreigners based on the law of treaties Indonesia as well as the role and responsibilities of a notary / PPAT in issuing deeds nominee agreement. Based on the results of research conducted by the author, so in this study showed that the nominee agreement in terms of acquisition of land by foreigners to borrow the citizen name is not valid since the beginning of the holding no bad faith agreement of the parties, contrary to the principle of freedom of contract by not qualify objective the validity of an agreement as provided for in Article 1320 of the Civil Code, and contrary to Article 9, Article 21 paragraph (1), and reaffirmed by Article 26 paragraph (1) BAL. Therefore, not the validity of the nominee agreement, legally do not have binding force means the juridical consequences of their actual nominee agreement violates the law and therefore null and void and the land fell to the state as required in Article 26 paragraph (2) BAL. The role of the Notary/PPAT in issuing deeds relating to a nominee agreement must still be based on the applicable rules. If the deeds issued by the Notary/PPAT detrimental to the party, then the Notary/PPAT can be requested, with overall responsibility for the losses.